Adrenal responses to a low‐dose short synacthen test in children with asthma. (22nd December 2014) - Hawcutt, Daniel B.; Jorgensen, Andrea L.; Wallin, Naomi; Thompson, Ben; Peak, Matthew; Lacy, David; Newland, Paul; Didi, Mo; Couriel, Jon; Blair, Jo; Pirmohamed, Munir; Smyth, Rosalind L.
Summary Objectives Corticosteroids are known to cause adrenal suppression. The aim of this study was to assess clinical factors affecting responses to a low dose short synacthen test (LDSST) in asthmatic children using corticosteroids. Design Patients were recruited from secondary care paediatric asthma populations within the UK. Patients Asthmatic children (5–18 years), receiving corticosteroids, underwent a LDSST (n = 525). Measurements Demographics and corticosteroid doses were tested for association with baseline and peak (stimulated) cortisol concentrations. Results Baseline cortisol was significantly associated with age (log baseline increased 0·04 nm per year of age, P < 0·0001), but not with gender or corticosteroid dose. Peak cortisol was significantly associated with total corticosteroid cumulative dose (decreased 0·73 nm per 200 mcg/day, P < 0·001) but not with age, gender inhaled/intranasal corticosteroid cumulative dose or number of courses of rescue corticosteroids. Biochemically impaired response (peak cortisol ≤500 nm) occurred in 37·0% (161/435) overall, including children using GINA low (200–500 mcg/day beclomethasone‐CFC equivalent 32%, n = 60), medium (501–1000 mcg/day (33%, n = 57) and high (>1000 mcg/day 40%, n = 13) doses of inhaled corticosteroid (ICS) similarly, and 36·6% of those using fluticasone ICS ≥500 mcg/day (71/194). Impaired response was more frequent in patients on regular oral corticosteroids (66%, n = 27, P < 0·001). Conclusion Children with asthma can develop biochemical adrenal suppression at similar frequencies for all ICS preparations and doses. The clinical consequence of biochemical suppression needs further study.